MODEL INTEGRATIF PENGUMPULAN DATA DALAM EVALUASI DAN SUPERVISI PENDIDIKAN - Corina Dwi Cahya Ningrum Jiwantoro; Mulyawan Safwandy Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Accurate, comprehensive, and relevant data collection is needed in educational evaluation and supervision so that improvement decisions do not rely on a single source of information. This study aims to describe the application of an integrative model of data collection methods and techniques in educational evaluation and supervision through observation, interviews, questionnaires, document analysis, and digital data. This study used a qualitative method with a descriptive approach at SMA Tunas Unggul. Data were collected through classroom observation, field notes, interviews, questionnaires, document review, and school digital data tracking. The data were analyzed qualitatively through data reduction, data display, and conclusion drawing. The results show that the integrative model can describe learning conditions more comprehensively because it combines various sources and data collection techniques. Observation showed that learning supervision had been implemented in a fairly structured way through schedules, instruments, and classroom observation. However, LMS use was not yet consistent across all subjects, the use of digital data for evaluation still varied, and follow-up actions from supervision results were not fully documented. Documents, interviews, questionnaires, and digital data served as comparison sources to strengthen the validity of the findings. The integrative model can serve as a systematic, adaptive, and contextual operational framework for supervisors and educational evaluators in developing improvement recommendations that are more objective, concrete, and evidence-based. Keywords: educational evaluation, educational supervision, observation, integrative model, qualitative method.